Yes SIRS or No SIRS? A Complication Following Cosmetic Medical Tourism. (31st January 2020) - Lineberry, Kyle; Punjabi, Ayesha; Becker, Devra B.
Background: Fat transfer for buttock augmentation has become popular in the last quarter century. Increasingly, patients obtain the surgery internationally and return home in the early post-operative period. Complications after procedures performed internationally can be difficult to manage due to a paucity of medical and surgical history as well as challenges in obtaining salient records such as operative reports or communicating with the initial surgical team. In the case of fat grafting, complications including infection, hematoma, and injury to critical structures can occur at both the recipient and donor sites. Case: A 28-year-old female underwent large volume buttock fat grafting in the Dominican Republic and received a post-operative course of oral levofloxacin and clindamycin. After her return home, she presented to our institution on post-operative day 9 with buttock pain, tachycardia, and leukocytosis. Imaging of her buttocks showed questionable fluid collections, with no drainable abscess. Drainage of the fat grafted areas by Interventional Radiology recovered a small amount of fluid with negative initial bacterial cultures. Despite antibiotic therapy with vancomycin and meropenem and fluid resuscitation, she did not experience clinical improvement and definitive treatment required bilateral debridement of buttocks with intraoperative findings of large volume fat necrosis. Cultures from the wound grew Peptostreptococcus after a week of incubation, and the patient recovered without further surgical intervention. The case suggests that immediate post-operative antibiotics can select for slow-growing organisms, and diagnosis of large volume fat graft necrosis may be delayed given the absence of a clear abscess cavity on imaging.